A discourse -structural analysis of Yorùbá proverbs in interaction - Ehineni, Taiwo Oluwaseun (Colombian Applied Linguistics Journal, 2016)
The subject of the proverb especially in the African context has been diversely explored by studies as Yankah (1989), Obeng (1996), Owomoyela (2005), and Fasiku (2006). This study, however, attempts a discourse and structural analysis of Yorùbá proverbs collected from oral interviews and native Yorùbá texts. First, based on a theory of the proverb as a discourse medium, the study reveals that proverbs are used to achieve different discourse acts and communicative goals by speakers. Native speakers use the proverb as a linguistic strategy of negotiating deep ideas and intentions. Second, the paper avers that the Yorùbá proverb is structurally characterized by some lexical and grammatical devices which help to reinforce its communicative intelligibility and textuality. Thus, it examines the Yorùbá proverb both functionally and formally and underscores that it is a culturally and linguistically rich significant part of the Yorùbá speech community.